Multimedia Applications Introduction Indonesian Traditional Musical Instruments Using Augmented Reality Technology With Marker Method Based Tracking: Multimedia Applications Introduction Indonesian Traditional Musical Instruments Using Augmented Reality Technology With Marker Method Based Tracking - Dendy Virgiawan; Mohammad Iwan Wahyuddin; Endah Tri Esthi (Jurnal Mantik, 2020)
The use of Augmented Reality as a medium for the introduction of Indonesian traditional musical instruments to Overcome the lack of introduction of traditional musical instruments, as well as increase of the value of understanding and provide a more interactive experience. An Augmented Reality-based introduction that displays 3D objects from traditional musical instruments. This application is made for smartphones using the Marker-Based Tracking method is the which is a part of the Augmented Reality that can be used in a marker pattern that will be read through a media tool for Android-based devices. Based on testing three devices, the application can run well, this application has a minimum specification operating system Android 5.1 (Lollipop) with a minimum of 1 GB of RAM.